An S-scheme heterojunction constructed from α-Fe2O3 and In-doped carbon nitride for high-efficiency CO2 photoreduction. Issue 5 (21st January 2022) - Wu, Jiaming; Li, Keyan; Li, Jiahui; Du, Jun; Li, Xiangyang; Song, Chunshan; Guo, Xinwen
Abstract : An S-scheme heterojunction is constructed with α-Fe2 O3 nanoparticles and In–CN nanosheets as a highly efficient photocatalyst for CO2 reduction. Abstract : The conversion of CO2 to chemicals and fuels by photocatalysis provides a promising strategy to solve both energy crisis and environmental problems, for which the development of high-activity photocatalysts is of particular importance. Herein, an S-scheme α-Fe2 O3 /In–CN heterojunction was constructed by combining α-Fe2 O3 nanoparticles with In-doped polymeric carbon nitride nanosheets, exhibiting excellent photocatalytic activity for CO2 reduction. Without any sacrificial agent and cocatalyst, the production rate of CO reaches 24.3 μmol g −1 h −1 with up to 94% CO selectivity. The construction of the S-scheme heterojunction promotes the charge separation and the light absorption of polymeric carbon nitride (PCN). The incorporation of In atoms in the framework of PCN enhances the CO2 adsorption and extends the lifetime of photogenerated charges. This work provides a new strategy for the design of high-performance photocatalytic materials.